Derrida's Wheel – The Circularity of Political (R)Evolutions. (January 2023) - Pusterla, Elia RG; Pusterla, Francesca
This article investigates the relationship between political revolutions and the evolution of politics. It discusses the circularity within the concept of revolution through Jacques Derrida's theory of sovereignty as particularly per Rogues – Two Essays on Reason and The Beast and the Sovereign. Derrida's notions of wheel and ipseity display ontological prerogatives and evolutionary limits of political revolutions possibly coinciding with reversals hard to turn into linear evolutions, excluding rather than reaffirming circularity. Political revolutions show such incapacity to become evolutionary for politics when lacking ontological substance and resting upon formal contingencies such as new techniques. An 'alturnative' notion of sovereignty is proposed as a heuristic criterion to gauge political events' 'revolutionary' quality. This undermines the (r)evolutionary nature of political turns, like those associated with the contemporary digitalisation of politics. The Italian Five Stars Movement's parable is a case in point of digital political turns whose effect is non-evolutionary for politics.